2013
DOI: 10.1902/jop.2012.120192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estrogen Deficiency and/or Caffeine Intake on Alveolar Bone Loss, Density, and Healing: A Study in Rats

Abstract: Caffeine increased BL in ligated teeth. Caffeine and/or estrogen deficiency decreased TBA in the unligated teeth and reduced BH after tooth extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 50 publications
5
31
1
1
Order By: Relevance
“…The most novel finding of the current study was the observation of the benefits of strontium ranelate on alveolar bone under estrogen deficiency. In agreement with previous studies, estrogen deficiency significantly increased the ligature‐induced BL. Strontium ranelate limited the ligature‐induced BL in the estrogen‐deficient animals at all experimental times and, to some extent, to an even greater magnitude than in the estrogen‐sufficient animals.…”
Section: Discussionsupporting
confidence: 93%
“…The most novel finding of the current study was the observation of the benefits of strontium ranelate on alveolar bone under estrogen deficiency. In agreement with previous studies, estrogen deficiency significantly increased the ligature‐induced BL. Strontium ranelate limited the ligature‐induced BL in the estrogen‐deficient animals at all experimental times and, to some extent, to an even greater magnitude than in the estrogen‐sufficient animals.…”
Section: Discussionsupporting
confidence: 93%
“…Estrogen deficiency results in loss of maxillary bone [8], [9], and estrogen receptor α is required to maintain the microarchitecture of the maxillary alveolar bone [10]. Estrogen is also reported to be an important regulator of cartilage homeostasis, growth and maturation [11], and controls the growth and closure of the epiphyseal plate [12].…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have suggested that the effects of coffee/caffeine on bone metabolism are still controversial (6), others have reported that caffeine, a major constituent of coffee, is associated with a significant increase of periodontal diseases (7), fracture of osteoporotic bones (8), increase in urinary calcium and decrease of bone mineral density (6), as well as delay in bone repair process (9). Also, caffeine has an additional deleterious effect when administrated to animals with osteoporotic bones (10).…”
Section: Introductionmentioning
confidence: 99%